ALKALINE PHOSPHATASE AS A SCREENING TEST FOR OSTEOMALACIA - Chinoy, Muhammad Amin; Javed, Muhammad Imran; Khan, Alamzeb; Sadruddin, Nooruddin (Journal of Ayub Medical College Abbottabad, 2011)
Background: Vitamin D deficiency remains common in children and adults in Pakistan despite adequate sunlight exposure. Diagnosis in adults is usually delayed and is made following pathological fractures that result in significant morbidity. The objective of this study was to see whether Serum Alkaline Phosphatase levels could be used as a screening test for osteomalacia. Methods: The Study was conducted at Fatima Hospital, Baqai Medical University, Gadap, Karachi, between July 2002 and June 2005. Serum calcium levels are commonly used to screen patients suspected of osteomalacia, and raised serum alkaline phosphatase (SALP) is considered a diagnostic finding. We used SALP to screen patients who presented with back or non-specific aches and pain of more than six months duration. Results: Three hundred thirty-four (334) patients were screened of which 116 (35%) had raised SALP. Osteomalacia was diagnosed in 92 (79.3%) of these 116 either by plain radiographs, bone biopsy or isotope bone scan. Fifty-four (53.4%) of the 101 cases had a normal level of serum calcium. Conclusions: Osteomalacia is likely to be missed if only serum calcium is used to screen patients. Serum Alkaline Phosphate should be used as the preferred method for screening these patients. Keywords: Osteomalacia, Metabolic bone disease, Serum Alkaline Phosphatase (SALP), Screening